Capital Structure and Firm Financial Performance: Moderating Effect of Board Financial Literacy in Nigerian Listed Non-Financial Companies - Tanko, Udisifan Michael; SIYANBOLA, Akeem Adetunji; Bako, Paul Matudi; DOTUN, Olalere Victor (Journal of Accounting Research, Organization and Economics, 2021)
Objective The study examined the moderating effect of board financial literacy on the relationship between capital structure and firm financial performance of listed non-financial companies in Nigeria. Design/methodology Capital structure was measured by long term debts to total assets, short term debts to total assets equity to total debt ratio and board financial literacy was measured by ratio of board members that have professional and academic qualification in accounting, finance and economics. Meanwhile financial performance was measured by return on assets. Secondary data was extracted from the sampled firms annual report and accounts and analyzed using Panel Least Square.Results The study revealed a positive and significant relationship between long term debt and ROA. It also shows that board financial literacy moderate capital structure significantly and increase firm performance. The study recommended that the management of Nigerian listed non-financial firms should optimize the capital structure in order to increase the financial performance. They can do that through ensuring that their capital structure is optimal by using more of current debts and non-current debt than equity. The Board of Directors of Nigerian listed company should be concerned about the level of long term debt, short term debt and include members that are financially literate who will contribute in financing decision of firm in order make optimal capital structure for better financial performance. This is because the findings of this study revealed a positive significant moderating relationship between long term debt, short term debt and financial performance.